2022
DOI: 10.1113/ep090029
|View full text |Cite
|
Sign up to set email alerts
|

High magnesium mitigates the vasoconstriction mediated by different types of calcium influx from monocrotaline‐induced pulmonary hypertensive rats

Abstract: Increased extracellular magnesium concentration has been shown to attenuate the endothelin-1-induced contractile response via the release of nitric oxide (NO) from the endothelium in proximal pulmonary arteries (PAs) of chronic hypoxic mice. Here, we further examined the involvement of Mg 2+ in the inhibition of vasoconstriction in PAs and distal smaller pulmonary arteries (sPAs) in a monocrotaline-induced pulmonary arterial hypertension (MCT-PAH) rat model. The data showed that in control rats vasoconstrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The vascular endothelium plays an important role in regulating vasomotor tone by synthesizing and releasing prostacyclin and NO [ 64 ]. Previous studies have shown that the relaxant action of magnesium was mediated by the endothelial release of NO [ 65 , 66 ]. Moreover, Mg 2+ can inhibit the depolarization effect of Ca 2+ and the excitation-contraction coupling related to Ca 2+ , so Mg 2+ can promote vascular relaxation of blood vessels by inhibiting Ca 2+ channels and their functions [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelium plays an important role in regulating vasomotor tone by synthesizing and releasing prostacyclin and NO [ 64 ]. Previous studies have shown that the relaxant action of magnesium was mediated by the endothelial release of NO [ 65 , 66 ]. Moreover, Mg 2+ can inhibit the depolarization effect of Ca 2+ and the excitation-contraction coupling related to Ca 2+ , so Mg 2+ can promote vascular relaxation of blood vessels by inhibiting Ca 2+ channels and their functions [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%